DETERMINANTS OF FOREIGN DIRECT INVESTMENT DEVELOPMENT - Elena Chirila - Donciu (CES Working Papers, 2013)
FDI had a strong impact in the last three decades on economic growth, foreign trade and production structures in almost all countries. The purpose of this paper is to analyze the main factors that contribute to attracting foreign direct investment flows and also the competitiveness of the business environment in Romania and its implications on investment decisions and economic growth. Research results show that the presence of FDI goes to those areas that can provide efficiencies investment factors: skilled and qualified labor, educational and research institutions etc..